Study of the Optimal Control of the Central Air Conditioning Cooling Water System for a Deep Subway Station in Chongqing - Xingyu Shu; Yu Dong; Jun Liu; Xinhua Xu (Buildings)
Cooling water, a crucial component of the central air conditioning setup, exerts a relatively minor direct impact on the thermal comfort of building indoor environments while it has a great effect on the system’s energy efficiency. Numerous studies exist on the cooling water system, particularly focusing on the process by which the cooling tower system operates, but the linkage between the chiller and the cooling tower is typically overlooked. When the connection is long and the passage environment for the pipeline is not conventional, it cannot be neglected for the optimal control for system efficiency improvement and energy consumption reductions. Throughout this research, a control strategy of the cooling water system for deep subway stations with long pipelines is presented. This cooling system was connected with outdoor cooling towers through a corridor about one hundred meters long. In this process, the cooling water temperature is influenced by the corridor’s thermal environment. For this study, an online control strategy optimizes the cooling water temperature, and a simulation platform of the air conditioning cooling water system of the deep subway station was also developed to evaluate the energy-saving potential of the control strategy of this cooling water system. Atop this platform, a simplified heat transfer model of the pipe corridor was created to determine the cooling capacity provided by the cooling water pipe in the corridor. The outcomes suggest that, as opposed to the conventional control mode, the energy-saving ratio of the optimal control strategy during a typical day may reach 4.1%, and the cooling source system’s Coefficient of Performance (COP) might see an increase of about 4.2%. The energy consumption of the water system throughout the whole cooling season may decrease by 9778 kWh, and the energy-saving rate is 4.1%. The results also demonstrate that the cooling water pipes release heat to the air in the corridor most of the time, and the released heat is larger than the absorbed heat. The maximum heat dissipation to the air in the corridor from the cooling water supply and return pipe can be up to 24.3 kW. The cooling effect of the corridor of subway stations with large depths below the ground surface cannot be ignored when optimal control is considered for the cooling water system.